A five year financial plan for Everfirst Loans Corporation - Mines, Rona Joyce T., Bumatay, Peavel Kate G., Igup, Ma. Cristina P., Lim, Herschel Kim P., Mabilangan, Michelle, Masilang, Marwin S., Moreno, Phoebe Kate L., Niza, May Angela D., Patron, Angelika C., Quintana, Deanne M., Reodique, Robel Mae S.,. 4 0 16; 5 (2017)
EXECUTIVE SUMMARY EverFirst Loans Corp. is a member of Lending Investors Federation which provides short-term pension loans to Social Security System (SSS) pensioners in the Philippines. The entity was established in 1997 and its first branch was in Novaliches. It is a non-stock corporation and is registered in Securities and Exchange Commission (SEC) IN November 2011 as a lending investor. At present, EverFirst Loans Corporation has 83 branches nationwide with more than 400 employees. The analysts used different methods and tools to identify the entity's problems. Such tools are horizontal and vertical analysis, trend analysis, financial ratios, altman's Z' Scores, and regression analysis. From the past five years, the entity has administrative expenses of 154%, 238.53%, 209.51% and 210.91%. Upon analyzing the entity's financial position, the analysts discovered that the entity is experiencing high operating costs from years 2011-2015 that hinders them from generating higher income. To achieve the financial objective, which is to lower the entity's operating cost by 28% for the next five (5) years, the analysts proposed Cost Minimization in order to reduce its expenditures. This will also help the entity improve its profitability to help the entity decrease its administrative expense by 18%, decrease in cost of revenue by 1% and increase the net income by 3.5 times for every succeeding year and improve the entity's cash flow.
Thesis: (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2